STRATEGY FOR INCREASING COMMUNITY PARTICIPATION IN DEVELOPMENT PLANNING IN BUALO VILLAGE PAGUYAMAN DISTRICT BOALEMO REGENCY - Mustofa; Djamila Podungge; Siske Anani (Journal of Economic, Business, and Administration (JEBA), 2024)
This study aims to identify and analyze strategies for increasing community participation in development planning in Bualo Village, Paguyaman District, Boalemo Regency. Community participation in Bualo Village has shown a significant declining trend, as evidenced by attendance rates in Village Development Planning Meetings (Musrenbang) which frequently fell below 50% between 2019 and 2021. Using a qualitative approach with SWOT analysis, this research finds that the village's primary strengths lie in the visionary leadership of the Village Head, the significant potential of the corn farming sector, and well-preserved local wisdom. However, these efforts are hindered by internal weaknesses such as budget limitations and a dependency on social assistance funds due to the impact of the Covid-19 pandemic. The main threats identified include low community attendance due to the prioritization of garden work, dependency on government aid, and participation fatigue resulting from unfulfilled aspirations. Recommended strategies include optimizing natural resources through integrated management, enhancing human resource capacity, and strengthening participatory governance that aligns local potential with formal planning mechanisms.